Serum Rankl/Osteoprotegerin Complex and Endothelial Progenitor Cells in Chronic Heart Failure - Berezin, Alexander E; Kremzer, Alexander A (Journal of Diagnostics, 2014)
The objectiveof this study was to assess an interrelationship serum RANKL/OPG complex with counts of circulating pro-angiogenic endothelial progenitor cells (EPCs) labeled as CD14+CD309+, and CD14+CD309+Tie2+ in patients with ischemic chronic heart failure (CHF). Methods: The study retrospectively evolved 153 patients (86 males) aged 48 to 62 years with exiting proven stable coronary artery disease (CAD). Systolic or diastolic CHF was defined among 109 (71.2%) patients. Twenty five 25 individuals were included in the control group. Circulating RANKL (sRANKL) and OPG were measured by high-sensitive ELISA kit at baseline. EPC populations were labeled by flow cytofluorimetry per High-Definition Fluorescence Activated Cell Sorter methodology. Results: Numerous of EPCs with phenotypes of CD14+CD309+ and CD14+CD309+Tie2+ were significantly lower in CAD patients when compared with healthy subjects. The trend to significant decrease of EPC numerous depending presence of CHF was found. The sRANKLlevel, OPG level, and sRANKL / OPG ratio were significantly higher in CHF subjects as compared to those without CHF (P=0.001). On multivariate analysis, CHF, sRANKL/OPG ratio, OPG, and NT-pro-BNP remained as independent predictors of decreased EPCs with phenotypes of CD14+CD309+ and CD14+CD309+Tie2+. When sRANKL/OPG ratio was added to the standard predictive model (CHF) improved relative integrated discrimination indices by 12.5% for CD14+CD309+ depletion, as well as by 17.3% for CD14+CD309+Tie2+depletion were found. Conclusion: We found that sRANKL/OPG ratio remained statistically significant predictor for depletion of pro-angiogenicEPCsin CAD patients.